The Development of Student Worksheet Materials Teaching in a Project-Based Learning Approach - Siti Nadifah; Hendri Raharjo; Indah Nursuprianah (MASI Mandiri Edukasi, 2022)
This study aims to describe the development of Student Worksheet materials teaching the Project Based Learning approach at MTs An-Nashuha Kalimukti Pabedilan-Cirebon Regency in mathematics learning on opportunity material. Mathematics learning is done by applying the project-based learning approach with a sample class of 35 students. The method used is the cluster random sampling technique, which takes clusters or groups, not based on population members taken one by one or individually. The use of data is a test instrument in the form of a pretest and posttest to measure the value of student results of learning outcomes and a questionnaire to determine student responses to the use of worksheets with the Project Based Learning approach. The pretest and posttest tests show that students have increased, Normal and homogeneous distribution. Furthermore, to determine the effectiveness of teaching materials, researchers used the Paired Sample t-Test. The Paired Sample t-Test calculation results showed a significance value of 0,000. Thus the significance value is smaller than 0.05, and 10.280 is more incredible than t table 2.04. Based on the results of the calculation of tcount> t-table, Ho is rejected. Because there are, there are differences in the average initial and final scores on the subject matter of opportunities and the use of Student Worksheet teaching materials as the development of materials teaching products are considered quite effective.